Pengaruh Sistem Kenaikan Pangkat dan Promosi Jabatan Terhadap Motivasi Kerja Pegawai Negeri Sipil di Propinsi Kepulauan Bangka Belitung - Ghoni, Abdul (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Aligning the Goals of the Government and Employees with career development, of course, the Employees will also get better in terms of skills and knowledge that are increasing and have a very clear impact on the Employees which will also impact the development of the government. Civil Servants / Civil Servants will also be able to get a higher position and the government will also get a better image. The people / society will see if the government is growing with the existence of civil servants / civil servants who are experts and experienced. For this reason, it is very important for both parties to improve themselves where the government will provide facilities and Civil Servants can increase their productivity. in this way, To be able to carry out public service tasks, government duties and development tasks, the government continues to make improvements to the management of civil servants which includes the preparation and determination of needs, procurement, ranks and positions, career development, career patterns, promotions , transfers, performance appraisals, salaries and allowances, rewards, discipline, dismissal, pension and old-age benefits, and protection (Law. No. 43 of 1999 in conjunction with Law. No. 5 of 2014). Therefore PP.99 of 2000 clearly regulates the provisions regarding the system, period, type, and terms of promotion, with the intention that in considering and determining the promotion of civil servants based on the same norms, standards and procedures in every agency. According to the latest data, there are about 5,373 Civil Servants/PNS in Bangka Belitung Province. The sample according to Arikunto (2006) is the totality or part or representative of the population to be studied. Furthermore, Arikunto (2006) added that if the population has more than 100 members, then it can be used as a sample using a simple random sample / probability random sampling, which is the research sample, so that it becomes a population study, and if the population is more than 100, then it can be taken between 10-15% or 2-2.5% and so on. Given that the population is more than 100, this study takes a simple random sample and not all members of the population are included in the sample, so this research is referred to as a Propability Random Sampling study of a population with a sample size of 107 employees in the Province Island Bangka Belitung.